From Evaluated Outputs to Values-Embedded Practices: The Power of Focusing on Process in Scholarly Communication - Agate, Nicky (Septentrio Conference Series, 2020)
See RECORDING. Currently, academia values what it can count: number of articles written, number of citations made, number of theses directed; number of euros or dollars received; in other words, it values what it can easily measure, and uses those numbers as a proxy for individual distinction within a competitive prestige economy. What if the individuals that make up the academic enterprise decided to focus on what we value, or purport to value (be that public scholarship, community engagement; openness and access; diversity, equity, and inclusion) instead? The HuMetricsHSS initiative promotes and supports one such alternative: a values-based, process-oriented approach to evaluative decision making in the academy, with a focus on the humanities and social sciences. Learn more about the history of the project, our current work, and our future plans in this talk.